“Türkiye” şiiri özelinde Osman Türkay’ın milliyetçilik ve Türkiye algısı - Şen, Can; Şen, Can (Söylem Filoloji Dergisi, 2022)
Edebiyatı şekillendiren temel dinamiklerden birisi ideolojilerdir. Yazarların ve şairlerin dünya görüşleri ya da ideolojileri reddeden apolitik tutumları, ele aldıkları konunun işlenişini ve sunuluşunu ciddi anlamda etkilemektedir. Milliyetçilik de önemli ideolojilerden biri olarak edebiyatı etkilemekte, şekillendirmektedir. Bu çalışmada Kıbrıs Türk edebiyatının önemli şairlerinden olan ve iki kez Nobel Edebiyat Ödülü’ne aday gösterilen Osman Türkay’ın (1927-2001) ilk şiir kitabı 7 Telli’de (1959) yer alan “Türkiye” şiiri milliyetçilik ve Türkiye algısı açısından incelenecektir. Şairin 1951’den 1958’e kadarki Türkiye ve İngiltere izlenimlerinin bir yansıması olan bu şiir, başındaki epigraflardan itibaren Türkay’ın milliyetçilik algısını ve bu doğrultuda o yıllarda İngiliz sömürgesi olan Kıbrıs’tan bağımsız Türkiye’ye bakışını somutlaştırması açısından önemlidir.

One of the basic dynamics shaping the literature is ideologies. World views or the apolitical attitude of the authors and the poets rejecting the ideologies seriously affect the examination or presentation of the subject they handle. Nationalism, being one of the important ideologies as well, affects and shapes the literature. In this study, the poem “Türkiye” in the first poetry book 7 Telli (1959) of Osman Türkay (1927-2001), who is one of the important poets of Cypriot Turkish literature and nominated for Nobel Literature Prize for twice, will be examined in terms of nationalism and perception of Turkey. This poem, which is a reflection of the poet's impressions of Turkey and England from 1951 to 1958, is important in terms of embodying Türkay's perception of nationalism as of the epigraphs at its beginning and accordingly his view of independent Turkey from Cyprus which was a British colony during those years.
Nationalism and Turkey perception of Osman Türkay specific to the poem “Türkiye”
Keywords: Kıbrıs Türk edebiyatı; Osman Türkay; Milliyetçilik; Şiir; Cypriot Turkish literature; Nationalism; Poem